2023
DOI: 10.17507/jltr.1405.15
|View full text |Cite
|
Sign up to set email alerts
|

Employers’ Perspectives of English-Major Students’ Weaknesses During Their Industrial Practicum

Phuong Hoang Yen,
Le Thanh Thao,
Ho Phuong Thuy
et al.

Abstract: In the 21st century, graduates are expected to have many employability skills to become successful employees in real-world settings. Before graduating, the industrial practicum is an excellent chance for employers to measure university students’ readiness for real jobs through their performances. Even though some studies have been conducted in this field, the topic is little studied from employers’ perceptions. This current study focused on employers’ reports on what English-major students lacked during their … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…This mismatch can lead to underemployment and a lack of job satisfaction among graduates, as well as a talent gap in the industry. Yen et al (2023) further explored this issue by analyzing employers' perceptions on the employability of Vietnamese English-major students in the context of a globalized economy. Their findings indicated that while graduates often possess strong theoretical knowledge, they may lack practical skills and hands-on experience that are increasingly sought after by employers.…”
Section: Vietnamese Job Market Dynamics and The Dynamics In Its Terti...mentioning
confidence: 99%
“…This mismatch can lead to underemployment and a lack of job satisfaction among graduates, as well as a talent gap in the industry. Yen et al (2023) further explored this issue by analyzing employers' perceptions on the employability of Vietnamese English-major students in the context of a globalized economy. Their findings indicated that while graduates often possess strong theoretical knowledge, they may lack practical skills and hands-on experience that are increasingly sought after by employers.…”
Section: Vietnamese Job Market Dynamics and The Dynamics In Its Terti...mentioning
confidence: 99%
“…The study employed triangulation under supervisors' and managers' perspectives then validated in the hands of analysts. Similarly, Yen et al, (2023) also conducted the same research. Their study concentrated on employer reports about English majors' experiences with their industrial practicums in Vietnam using qualitative methods such as focus-group interviews.…”
Section: Introductionmentioning
confidence: 96%